2014
DOI: 10.1093/geronb/gbu162
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sleep Predict Changes in Affect in Older Caregivers of Individuals with Alzheimer’s Dementia: A Multilevel Model Approach: Table 1.

Abstract: Examining older caregivers' daily sleep/affect association is important, because caregiving-related awakenings are unavoidable, often unpredictable, and can impact mood. Future research is needed to examine whether regularization in awakenings and/or negative affect represent important secondary, or even target, treatment outcomes for this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Impaired melatonin production occurs in AD and other dementias because of Suprachiasmatic Nucleus neuronal loss (469;470), leading to a decreased regularity of sleep, impaired sleep initiation and continuity, and difficulty maintaining wakefulness during daylight. Sleep disturbance predicts family carer depressive symptoms, increases care burden and leads to care home admission, significantly elevating care costs (471). A Cochrane review found no definitive evidence from trials of pharmacological treatments for sleep in older people with dementia (ChEIs, donepezil and galantamine; antidepressants, trazodone and mirtazapine; or melatonin and ramelteon) and there were no RCTs of benzodiazepines or non-benzodiazepine hypnotics (472).There was some suggestion that trazodone 50mg may be useful but no large trials.…”
Section: Sleepmentioning
confidence: 99%
“…Impaired melatonin production occurs in AD and other dementias because of Suprachiasmatic Nucleus neuronal loss (469;470), leading to a decreased regularity of sleep, impaired sleep initiation and continuity, and difficulty maintaining wakefulness during daylight. Sleep disturbance predicts family carer depressive symptoms, increases care burden and leads to care home admission, significantly elevating care costs (471). A Cochrane review found no definitive evidence from trials of pharmacological treatments for sleep in older people with dementia (ChEIs, donepezil and galantamine; antidepressants, trazodone and mirtazapine; or melatonin and ramelteon) and there were no RCTs of benzodiazepines or non-benzodiazepine hypnotics (472).There was some suggestion that trazodone 50mg may be useful but no large trials.…”
Section: Sleepmentioning
confidence: 99%
“…This affects sleep regardless of whether a person has assistance at home or is in a hospital intensive care unit . For those who have assistance at home, there are genuine concerns that their caregiver's sleep is also affected …”
Section: Sleep and Physical Disabilitymentioning
confidence: 99%
“…Technological strategies that might help reduce the unpredictability of dealing with care-receivers at night could be particularly helpful as there is evidence that caregiver perceptions about the inconsistency in their sleep may have as much impact on caregiver mood and burden as the actual sleep quality itself [40].…”
Section: Caregiver Sleep Interventionsmentioning
confidence: 99%